2020
DOI: 10.1175/jpo-d-19-0194.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and Formation of Barrier Layers and Associated Temperature Inversions in the Eastern Tropical North Pacific

Abstract: Seasonality and formation of barrier layers (BLs) and associated temperature inversions (TIs) in the eastern tropical North Pacific Ocean were investigated using raw and gridded Argo profiling float data, satellite data, and various sea surface flux data. BLs were observed frequently in boreal summer and autumn along the sea surface salinity (SSS) front south of the eastern Pacific fresh pool. TIs were found within the gap between the western and eastern Pacific warm pools in autumn when BLs were thickest. A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 69 publications
6
12
0
Order By: Relevance
“…The maximum BLT in the mean is found in the equatorial western Pacific Ocean (about 30 m) and decreases eastward (about 10 m near 140°W). Note that this is the mean picture, which may reflect that the BL is only seasonally or sporadically present, such as in the eastern Pacific Ocean (e.g., Katsura & Sprintall, 2020), or alternatively that the ECCO vertical resolution is not sufficient to resolve the thin BLTs and shallow MLDs in this region.…”
Section: Mean State Of the Equatorial Pacific Oceanmentioning
confidence: 99%
“…The maximum BLT in the mean is found in the equatorial western Pacific Ocean (about 30 m) and decreases eastward (about 10 m near 140°W). Note that this is the mean picture, which may reflect that the BL is only seasonally or sporadically present, such as in the eastern Pacific Ocean (e.g., Katsura & Sprintall, 2020), or alternatively that the ECCO vertical resolution is not sufficient to resolve the thin BLTs and shallow MLDs in this region.…”
Section: Mean State Of the Equatorial Pacific Oceanmentioning
confidence: 99%
“…In fact, some signals seen in EN4‐derived BLT have no correspondence in the profiles that serve as basis for the objective analysis. Studies suggest that interpolation of in situ profile data in gridded data sets creates BLT artifacts (de Boyer Montégut et al., 2007; Katsura & Sprintall, 2020; Mignot et al., 2007; Sato et al., 2006). We take therefore the EN4 results as being only illustrative rather than giving true BLT amplitudes.…”
Section: Comparison Between Observed and Simulated Barrier Layersmentioning
confidence: 99%
“…In an analysis of Argo observations from January 2000 to June 2005, Sato et al (2006) noticed patchy and thick barrier layer structures, which were explained by large-scale and small-scale (100 km) subduction processes in the subtropical gyres of the World Ocean. As those synoptic thick barrier layers appear in areas where the quasi-permanent climatological barrier layer is also thick, the climatological barrier layer is claimed to be a spatially and temporally smoothed picture of the synoptic barrier layers ( de Boyer Montégut et al, 2007;Katsura & Sprintall, 2020;Mignot et al, 2007;Sato et al, 2006). According to the authors, since the Argo floats sample mesoscale features but do not resolve them, the role of mesoscale eddies to describe the barrier layer formation process needs to be assessed.…”
mentioning
confidence: 99%
“…A seasonal climatological study of BLs and TIs based on Argo profiling float data by Katsura and Sprintall (2020; henceforth KS2020) revealed that BLs are distributed along the SSS front south of the EPFP with a seasonal peak in boreal summer and autumn. Bingham et al (2020) show an example of this from a high-resolution model.…”
Section: Katsura Et Almentioning
confidence: 99%